2020
DOI: 10.1002/aisy.201900178
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Calibration of Soft Sensors Using Optimal Transportation Transfer Learning for Mass Production and Long‐Term Usage

Abstract: Soft sensors suffer from high manufacturing tolerances and signal drift from long‐term usage, which degrades their practicality. Although deep learning has recently been proposed to address these issues, it is expensive in terms of data collection and processing. Therefore, an adaptive calibration method is proposed for soft sensors, suitable for mass production and long‐term usage. In addition to maintaining the original benefits of deep learning characterization, this method enables fast and accurate calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…An automated manufacturing process, such as direct patterning of liquid conductors (12,68,86) or embedded 3D printing (18,87,88), will be highly useful to increase the uniformity of the product in this case. Furthermore, a transfer learning technique (89) can be used for calibrating multiple sensors with variations more efficiently, which will save a considerable amount of time and resources when compared with traditional calibration methods.…”
Section: Discussionmentioning
confidence: 99%
“…An automated manufacturing process, such as direct patterning of liquid conductors (12,68,86) or embedded 3D printing (18,87,88), will be highly useful to increase the uniformity of the product in this case. Furthermore, a transfer learning technique (89) can be used for calibrating multiple sensors with variations more efficiently, which will save a considerable amount of time and resources when compared with traditional calibration methods.…”
Section: Discussionmentioning
confidence: 99%
“…This learning method was able to reduce training time and efficiently process large dataset, while maintaining superior sensing performance. Kim et al also used an optimal transportation transfer learning to learn the model of soft sensors with large volume [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the level of abstraction of the entire robotic system, Van Meerbeek et al tested various learning algorithms to estimate the twist and bend angles in sensorized foam, finding that k nearest neighbors (kNN) outperformed other common algorithms including support vector machines (SVM) and multilayer perceptrons (MLP) (55). In addition, Kim et al, Soter et al, Thuruthel et al, and Kim et al, focused on recurrent neural networks, which have been shown to be advantageous for learning patterns in time series data (9,12,64,65).…”
Section: Machine Learning For Soft E-skinsmentioning
confidence: 99%